2019
DOI: 10.1128/iai.00273-19
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella enterica Serovar Panama, an Understudied Serovar Responsible for Extraintestinal Salmonellosis Worldwide

Abstract: In recent years nontyphoidal Salmonella has emerged as one of the pathogens most frequently isolated from the bloodstream in humans. Only a small group of Salmonella serovars cause this systemic infection, known as invasive nontyphoidal salmonellosis. Here, we present a focused minireview on Salmonella enterica serovar Panama, a serovar responsible for invasive salmonellosis worldwide. S. Panama has been linked with infection of extraintestinal sites in humans, causing septicemia, meningitis, and osteomyelitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 63 publications
(104 reference statements)
1
18
0
Order By: Relevance
“…Typhoid toxin was first found in serovar Typhi, and only limited serovars, including at least 47 NTS serovars from multiple serogroup or clades, carry unique toxins [38–41]. Interesting, serovar Panama, which was recently recognized as an extraintestinal iNTS, also carries cytolethal distending toxin (CDT) homology [41, 42]. Here, our comparative genomics approach, for the first time, revealed that all S .…”
Section: Discussionmentioning
confidence: 99%
“…Typhoid toxin was first found in serovar Typhi, and only limited serovars, including at least 47 NTS serovars from multiple serogroup or clades, carry unique toxins [38–41]. Interesting, serovar Panama, which was recently recognized as an extraintestinal iNTS, also carries cytolethal distending toxin (CDT) homology [41, 42]. Here, our comparative genomics approach, for the first time, revealed that all S .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, ST313 L3 had an elevated invasiveness index compared to ST313 L2, unlike the UK-isolated ST313 strains that had a lower invasiveness index than ST313 L2 47 . The majority of genes unique to ST313 L3 were plasmidor prophage-encoded, including by the prophage RE-2010 29 which is found in other extraintestinal Salmonella pathovariants [30][31][32] . Apart from accessory genome composition, other ST313 L3-specific changes involve loss-of-function SNPs in genes that are not required for systemic infection.…”
Section: Nature Microbiologymentioning
confidence: 99%
“…They are also typical for poultry but rather atypical for cattle farms [24]. The serovar S. Panama is reported to be most susceptible to antibiotics in Germany (except for streptomycin) but can be multi-resistant as reported from Asia and South America [2,5,25,26]. We present here a new rare clone of this serovar with an acquired antibiotic resistance.…”
Section: Discussionmentioning
confidence: 64%
“…enterica serovar Panama (S. Panama) was first isolated during an analysis of a food-borne infection in Panama in 1934 [1]. The serovar Panama is rarely discussed but has a strong association with invasive diseases and is linked with infections in humans [2]. S. Panama is known to cause a significant proportion of Salmonella infections in the pig industry [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation